Identification and activity of active compound of bamboo leaves (Bambusa vulgaris Schrad ex.J.C) ethanolic extract against diabetic ulcers gram-negative bacteria from diabetic ulcer’s patient - Pratiwi Apridamayanti (Universitas Islam Indonesia, 2021)
Abstract Background: Bamboo leaves (Bambusa vulgaris Schrad ex.J.C) are plants that are known to have pharmacological activity, one of which is to have antibacterial activity. Diabetic Foot Ulcers (DFU) is one chronic complication of diabetes mellitus. DFU is open sores on the surface of the skin that can be accompanied by local tissue death. Infection that is not appropriately treated in patients can cause amputation. Improper use of antibiotics can cause resistance events. A resistance that occurs in Proteus mirabilis, Pseudomonas aeruginosa, and Escherichia coli in isolates from DFU patients encourages researchers to look for alternative antibiotics from natural resources.Objective: Determine the profile of secondary metabolites by thin-layer chromatography, foam index, total phenols, total flavonoids and the antibacterial activity of bamboo (B. vulgaris) through the antibacterial with clear zone value of bamboo leaf ethanol extract against bacteria E. coli, P. aeruginosa, and P. mirabilis.Method: Phenol, flavonoid, and triterpenoid test using TLC method. Saponin tests were carried out using foam index, fish index, and hemolytic index test methods. Total flavonoid testing using Chang method and total phenol method using the Follin Ciocalteau reagent then proceed using a spectrophotometer. Test the antibacterial activity using the agar diffusion method.Results: Chromatographic profile, phenol, flavonoid, and triterpenoid compounds were obtained; saponin index obtained foam index of 333; fish index of 200; and the hemolytic index of 1,111. The total phenol test was 16.052 ± 3.12 % and the total flavonoid was 2.42 ± 0.44 %. Antibacterial activity test obtained MIC values of 60 mg/ml for E. coli bacteria; 100 mg/ml for the bacterium P. aeruginosa; and 30 mg/ml of P. mirabilis.Conclusion: The content of secondary metabolites found in the ethanol extract of bamboo leaves were flavonoid, phenol, saponin and triterpenoids. Ethanol extract of bamboo leaves has a the potential to produce antibacterial activity against gram-negative pathogenic bacteria isolated from diabetic wound patientsKeywords: Bambusa vulgaris Schrad ex.J.C, total phenol, total flavonoid, MIC Intisari Latar belakang: Daun bambu (Bambusa vulgaris Schrad ex.J.C) merupakan tumbuhan yang diketahui memiliki aktivitas farmakologis, salah satunya adalah memiliki aktivitas antibakteri. Ulkus Kaki Diabetik (UKD) adalah salah satu bentuk komplikasi kronik diabetes melitus berupa luka terbuka pada permukaan kulit yang dapat disertai adanya kematian jaringan setempat. Infeksi yang tidak ditangani dengan baik pada penderita dapat menyebabkan terjadinya kasus amputasi. Penggunaan antibiotik yang tidak tepat dapat mendorong peristiwa resistensi. Resistensi yang terjadi pada Proteus mirabilis, Pseudomonas aeruginosa dan Escherichia coli pada isolat pasien UKD mendorong peneliti untuk mencari alternative antibiotik yang bersumber dari bahan alam.Tujuan: Mengetahui profil metabolit sekunder secara kromatografi lapis tipis, indeks busa, total fenol, total flavonoid dan aktivitas antibakteri bambu (B. vulgaris) melalui nilai Kadar Hambat Minimum (KHM) ekstrak etanol daun bambu terhadap bakteri E. coli, P. aeruginosa dan P. mirabilis.Metode: Uji Fenol, Flavonoid dan Triterpenoid menggunakan metode KLT. Pengujian saponin dilakukan dengan metode uji indeks busa, indeks ikan, dan indeks hemolitik. Pengujian Flavonoid total menggunakan metode Chang dan Fenol total dengan menggunakan reagen Follin Ciocalteau kemudian dilanjutkan dengan menggunakan spektrofotometer. Uji aktivitas antibakteri dengan menggunakan metode difusi agar. Hasil: Pada profil kromatografi diperoleh senyawa fenol, flavonoid, dan triterpenoid; indeks saponin diperoleh indeks busa sebesar 333; indeks ikan sebesar 200; dan indeks hemolitik sebesar 1.111. Pengujian fenol total sebesar 16,05±3,12% Asam Galat Ekuivalen (AGE)dan Flavonoid total sebesar 2,42±0,44% Kuarsetin Ekuivalen (KE). Uji aktivitas antibakteri diperoleh nilai MIC sebesar 60 mg/ml untuk bakteri E. coli ; 100 mg/ml untuk bakteri P. aeruginosa ; dan 30 mg/ml P. mirabilis.Kesimpulan: Kandungan metabolit sekunder yang terdapat pada ekstrak etanol daun bambu adalah flavonoid, fenol, saponin, dan triterpenoid. Ekstrak etanol daun bambu memiliki potensi menghasilkan aktivitas antibakteri terhadap bakteri patogen gram negatif isolat pasien luka diabetesKata kunci : Bambusa vulgaris Schrad ex.J.C, fenol total, flavonoid total, KHM